Association of Traumatic Events, Post Traumatic Stress Disorder and Sexual Autonomy among Female University Students of North Korean Defectors - Young Jin Lee; Hae Won Kim (Korean Society of Women Health Nursing, 2019)
PURPOSE: To determine associations of traumatic events and post-traumatic stress disorder (PTSD) with sexual autonomy and identify factors influencing sexual autonomy among female university students of North Korean defectors. METHODS: A cross-sectional, descriptive study was performed with a total of 103 female students who completed a structured online self-report survey from January 7 to March 31, 2018. This study was conducted using questionnaires on interpersonal trauma scale, the Traumatic Scale for North Korean Refugees (TSNKR), and sexual autonomy measurement for college students. Data were analyzed using descriptive statistics, t-test, one-way ANOVA, Pearson's correlation coefficients, and multiple linear regression with SPSS WIN 23.0 program. RESULTS: Traumatic events, PTSD, and sexual autonomy scores were 3.96±3.07, 31.47±10.75, and 52.66±6.89, respectively. PTSD was positively correlated with traumatic events (r=.22, p=.030). Sexual autonomy was inversely correlated with PTSD (r=−.25, p=.010). Contraceptive use, PTSD, and voluntary sexual debut explained 26% of sexual autonomy of participants. CONCLUSION: To improve sexual autonomy of young women from North Korea, reproductive intervention programs including contraception, sexual assertiveness training, and psychoeducation to reduce PTSD need to be developed and implemented.